Mormolyce matejmiciaki sp. nov. (Coleoptera: Carabidae: Lebiinae) from Borneo - Ďuríček, Marek; Klícha, Miroslav (Zootaxa, 2017)
Mormolyce matejmiciaki sp. nov. from Borneo (Kalimantan Utara province) is described and illustrated. The new species is also compared with other members of the genus Mormolyce Hagenbach, 1825, and a key to species of this genus is provided.